Effects of Tuina Massageand Johnson Massage on Weight Gain in Babies Aged 0-12 Months - Boleo, Daswi; Lisca, Shinta Mona; Sugesti, Retno; Novalia, Khumaedah; Noviyanti, Noviyanti; Shany, E. Melda; Febriyanti, Rizka (Universitas Prima Indonesia, 2025)
The first year of life is a crucial phase in a child’s growth and development, where proper nutrition and sensory stimulation significantly influence physical outcomes, such as weight gain. Infant massage is one of the tactile stimulations that can help improve weight and overall well-being. This study aims to examine and compare the effects of Tuina massage and Johnson's massage on the weight gain of infants aged 0–12 months at the Patia Public Health Center, Pandeglang, in 2025. A quasi-experimental design with a one-group pretest-posttest approach was employed. Thirty infants were selected using purposive sampling and divided into two intervention groups, with 15 infants receiving Tuina massage and 15 receiving Johnson's massage. The massages were conducted three times over a two-week period. Data were collected using observation sheets and body weight measurements before and after the intervention. The results revealed that both massage techniques significantly increased infant weight. Infants who received Tuina massage experienced an average weight increase from 5.607 kg to 6.687 kg, while those who received Johnson’s massage increased from 4.840 kg to 5.933 kg. Statistical analysis using the Paired Sample T-Test showed a significant difference between the two methods (p = 0.025), indicating that Tuina massage was more effective. In conclusion, both Tuina and Johnson's massage positively affect infant weight gain, with Tuina showing greater efficacy in promoting infant growth.